Springback Analysis in Bending of V-Section Using Deformable Die - Shukur, Jalil; Khudhir, Waqass; Abbood, Mohanad (Al-Nahrain Journal for Engineering Sciences, 2022)
With the development of manufacturing techniques, the demands have increased on tools with flexible components that can produce parts with different shapes and sizes only by replacing the rigid part of these tools, since the flexible part can match the required geometry. This study is focused on effects of rubber hardness and sheet thickness on the springback developed on the produced parts. Silicone rubber with three hardness (40,60 ,80) Shore A hardness scale was used. The material of workpiece was Aluminum (3003) with three different thicknesses of (0.8,1,1.2) mm and three holding time of (0,10,20) seconds. The results demonstrate that, the springback decreases with any increase in the rubber hardness or sheet thickness. In addition, the holding time showed a significant effect only with a harder rubber.